Analysis of Factors Influencing Laboratory Practices on Semester IV DIII Nursing Students at Aisyiyah Palembang Health College in 2024 - Indah Noer Jannah; Rahmania Ambarika; Ratna Wardani (Jurnal Ners, 2025)
This study analyzes factors influencing laboratory practice performance among fourth-semester D3 Nursing students at STIKES Aisyiyah Palembang in 2024. Using a cross-sectional design with random sampling, 131 students participated by completing structured questionnaires. Data were analyzed with simple linear regression to determine the effects of motivation, interest, and learning intensity on laboratory outcomes. Results showed that 64.9% of students had positive motivation, 66.4% expressed strong interest, and only 13.7% demonstrated high learning intensity. Overall, 94.7% of students passed laboratory practice. Cross-tabulation revealed that students with positive motivation (97.6%), strong interest (97.7%), and high learning intensity (100%) had the highest pass rates. Regression analysis confirmed that motivation (p = 0.000), interest (p = 0.000), and learning intensity (p = 0.035) significantly influenced laboratory performance, while the learning environment and facilities showed no statistical impact. These findings highlight that intrinsic factors—particularly motivation and interest—are stronger predictors of success compared to external conditions. Therefore, nursing educators should prioritize strategies that foster student motivation, maintain engagement, and encourage consistent learning intensity to optimize laboratory outcomes.